Pt- and TCO-free flexible cathode for DSSC from highly conducting and flexible PEDOT paper prepared via in situ interfacial polymerization - Anothumakkool, Bihag; Agrawal, Ishita; Bhange, Siddheshwar N.; Soni, Roby; Game, Onkar S.; Ogale, Satishchandra B.; Kurungot, Sreekumar (ACS Applied Materials & Interfaces, 2016)
Here, we report the preparation of a flexible, free-standing, Pt- and TCO-free counter electrode in dye-sensitized solar cell (DSSC)-derived from polyethylenedioxythiophene (PEDOT)-impregnated cellulose paper. The synthetic strategy of making the thin flexible PEDOT paper is simple and scalable, which can be achieved via in situ polymerization all through a roll coating technique. The very low sheet resistance (4 Omega/square) obtained from a film of 40 mu m thick PEDOT paper (PEDOT-p-5) is found to be superior to the conventional fluorine-doped tin oxide (FTO) substrate. The high conductivity (357 S/cm) displayed by PEDOT-p-5 is observed to be stable under ambient conditions as well as flexible and bending conditions. With all of these features in place, we could develop an efficient Pt- and TCO-free flexible counter electrode from PEDOT-p-5 for DSSC applications. The catalytic activity toward the tri-iodide reduction of the flexible electrode is analyzed by adopting various electrochemical methodologies. PEDOT-p-5 is found to display higher exchange current density (7.12 mA/cm(2)) and low charge transfer resistance (4.6 Omega) compared to the benchmark Pt-coated FTO glass (2.40 mA/cm(2) and 9.4 Omega, respectively). Further, a DSSC fabricated using PEDOT-p-5 as the counter electrode displays a comparable efficiency of 6.1% relative to 6.9% delivered by a system based on Pt/FTO as the counter electrode.
Keywords: counter electrode; dye-sensitized solar cell; flexible and thin devices; impedance analysis; interfacial polymerization; polyethylenedioxythiophene